"Blighted Futures: The Soybean Assemblage and Argentina's Agro-extractive Turn". Issue 141 (May 2023) - Smith, Geneva M.
Highlights: Articulates Argentina's "soybean assemblage." The assemblage consists of GM soy, soil, agrochemicals, producers, Kirchnerism, and agronomy. Assemblage theory emphasizes the non-human aspects of Argentina's GM soy boom. Examines GM soybean producers who believe they are locked into GM soybeans. Adds to development studies through attention to an agricultural assemblage. Abstract: Argentine GM soybean producers find themselves in an untenable situation. They must produce more even though pressures like weed resistances, global commodities price fluctuations, and an unpredictable tax regime pose ever greater challenges. Meanwhile, public sentiment has largely turned against the rural sector for its opposition to tax increases and the under-regulated use of agrochemicals. There are, however, no easy alternatives now that producers find themselves in the grips of this agro-economic complex. Argentine GM soybean producers' experiences of how they arrived at a point of agro-extractivist lock in is the focus of this article. To better understand their perspectives, this article elaborates the "soybean assemblage." This consists of histories, politics, actors, and more-than-human agents that stabilized the GM soybean industry in Argentina, keep it in place, and render it fragile. This includes how autogamous soybeans and an intellectual property regime function in Argentina, the country's famously fertile land and its position within the national imaginary, Kirchnerist politics that rely on soybean exports to fund social programs, producers' economic interests and sense of duty to the nation, the discipline of agronomy as a site of agrochemical knowledge production, and how agrochemicals, namely glyphosate, created long-term dependence under the guise of safe use.